Full-truthful implementation in Nash equilibria - Hideki Mizukami; Takuma Wakayama (Osaka University, Institute of Social and Economic Research (ISER), 2006)
We consider full-truthfulNash implementation, which requires that truth telling by each agent should be a Nash equilibrium of a direct revelation mechanism, and that the set of Nash equilibriumoutcomes of the mechanismshould coincide with the f-optimal outcome. We showthat restricted monotonicity together with an auxiliary condition called boundedness is both necessary and sufficient for full-truthful Nash implementation. We also prove that full-truthful Nash implementation is equivalent to secure implementation (Saijo et al. (2005)). This gives us an alternative characterization of securely implementable social choice functions.
Keywords: 330; Restricted Monotonicity; Direct Revelation Mechanisms; Nash Implementation; Truthful Implementation; Secure Implementation; Nash-Gleichgewicht; Neue politische Ökonomie